Case Report: A rare cause of duodenal intussusception: the pedunculated Brunner’s gland hamartoma - Wang, Yi-Hua; Zhou, Jing; Huang, Xiao-Shan; Zheng, Xiao-Zhong; Gu, Meng-Ying; Duan, Jia-Qi; Fan, Shu-Feng; Xu, Jian-Xia (Frontiers in Oncology, 2025)
BackgroundBrunner’s gland hamartomas (BGHs) are primarily benign and typically do not exhibit characteristic clinical symptoms. The discovery and diagnosis of duodenal BGHs may require imaging assistance. Dissemination of this case can help inform future diagnosis and effective treatment.Case summaryHerein, we report a case of a 43-year-old man presenting with bloating. The computed tomography (CT) found a strip-like, mixed-density lesion with fat attenuation in the duodenal canal, and the proximal intestine was dilated. Contrast-enhanced abdominal CT revealed that the lesion had mild to moderate enhancement with incomplete intussusception. The lesion was resected entirely with the endoscope. Postoperative pathology results confirmed a BGH.ConclusionCT findings exhibit specific characteristics that are valuable for visualizing these lesions or their secondary manifestations. An elongated intraluminal mass lesion with heterogeneous density and fat attenuation may indicate a pedunculated duodenal Brunner’s gland hamartoma.